Woody flora diversity and carbon sequestration potential of university of ibadan teak plantation: a consideration for climate change mitigation in southwest nigeria (2016)
Increase in atmospheric C02 is largely attributable to forest loss and carbon emission activities. Ability of forest plantations to sequester carbon for climate change mitigation is central to climate change mitigation, thus the study investigated carbon sequestration capacity of University of Ibadan Teak Plantation. The plantation (0.305 km2) is situated in a rainforest zone in Ibadan, Nigeria on 7°27'25.18'N; 3°54 14.04' E and a meaneievation of 209 m above sea level. Systematic sampling of 63 plots, each measuring 225 m2 was conducted on trees of >5 m bole height, >10 cm girth at breast height. Plots were distributed at 25 m intervals along seven line transects laid at 85 m apart. Species identification, relative importance value (RIV), diversity, multivariate analyses and carbon sequestration capacity of the forest were determined using standard procedures. Eighteen tree species in 12 families were enumerated. Tectonagrandis had highest RIV (49.347) with high dominance in many plots. Evenness index was generally low (below 0.5). Ordination biplotsindicated a mixed plantation. The carbon stock in the plantation was low (19.768 kg/ha/annum) compared to a typical tropical rainforest (600 kg/ha/annum), indicating 3.295% of carbon sequestration efficiency (CSE). The CSE of the plantation was low. This low CSE could be enhanced with adequate stocking density and removal of anthropogenic disturbances.